Malawi’s agrifood system structure and drivers of transformation - Diao, Xinshen; De Weerdt, Joachim; Duchoslav, Jan; Pauw, Karl; Thurlow, James; Ellis, Mia (International Food Policy Research Institute, 2023)
Malawi experienced modest growth from 2009 to 2019, with average annual GDP growth of 4.7 percent. The global COVID-19 pandemic caused a significant slowdown in 2020 and 2021, and the economy has not yet rebounded to pre-pandemic levels (World Bank 2023). At the time of writing, GDP is projected to grow at 2.4 percent in 2023, which in combination with population growth of 2.7 percent would result in a 0.3 percent contraction of GDP per capita (IMF 2023). At the core of the failure to resume pre-pandemic economic growth rates are a worsening debt crisis, a balance of payment crisis, an acute shortage of foreign exchange reserves, and several external shocks (World Bank 2022). The latter include the effects of the Russia-Ukraine conflict and the devastation caused by cyclone Freddy in 2023 (De Weerdt and Duchoslav 2022; Diao et al. 2022).